A Comparative Analysis of One-Sided Violence and Civil War Peace Agreement Implementation. Issue 1 (29th May 2020) - Joshi, Madhav
Does one-sided violence create a negative cascading effect on the success of peace agreement implementation? If violence influences peace accord implementation negatively, how can such violence be contained to safeguard the implementation process? While post-conflict one-sided violence can be viewed as residual, the use of such violence can significantly influence peacebuilding outcomes. Implementing the agreement is a contentious process as both sides expect to maximize their benefits and minimize their losses from intended reforms negotiated in the agreement. Implementation success is achieved by minimizing the difference in policy reforms through mutual trust, reciprocity, and sequential policy moves. In such a contentious implementation setting, the use of one-sided violence by any actor undermines trust and reciprocity between signatories and subsequently forestalls implementation success. Empirical analyses of a global sample of comprehensive peace agreements since 1989 show a significant and negative relationship between the use of one-sided violence and the peace agreement implementation rate. Rebel one-sided violence has a larger negative effect on implementation compared to state and other non-state one-sided violence.